Targeted high throughput sequencing in clinical cancer settings: formaldehyde fixed-paraffin embedded (FFPE) tumor tissues, input amount and tumor heterogeneity - Kerick, Martin; Isau, Melanie; Timmermann, Bernd; Sültmann, Holger; Herwig, Ralf; Krobitsch, Sylvia; Schaefer, Georg; Verdorfer, Irmgard; Bartsch, Georg; Klocker, Helmut; Lehrach, Hans; Schweiger, Michal R. (BMC medical genomics, 2011)
Massively parallel sequencing technologies have brought an enormous increase in sequencing throughput. However, these technologies need to be further improved with regard to reproducibility and applicability to clinical samples and settings.